2020
DOI: 10.1088/1361-6528/ab6fd6
|View full text |Cite
|
Sign up to set email alerts
|

Silicon oxide-niobium oxide mixture films and nanolaminates grown by atomic layer deposition from niobium pentaethoxide and hexakis(ethylamino) disilane

Abstract: Amorphous SiO2-Nb2O5 nanolaminates and mixture films were grown by atomic layer deposition. The films were grown at 300 o C from Nb(OC2H5)5, Si2(NHC2H5)6, and O3 to thicknesses ranging from 13 to 130 nm. The niobium to silicon atomic ratio was varied in the range of 0.11-7.20. After optimizing the composition, resistive switching properties could be observed in the form of characteristic current-voltage behavior. Switching parameters in the conventional regime were well defined only in a SiO2:Nb2O5 mixture at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Using O 3 as an oxygen source for growth of Nb 2 O 5 with Nb (OEt) 5 has, however, remained unexplored until very recently, when Kukli et al utilized O 3 to deposit multilayers of SiO 2 + Nb 2 O 5 for use as a switching media. 25,26 This study confirms that the O 3 process provides films with very low hydrogen content, albeit very little is known regarding the mechanism of growth. As a starting point, we confirmed that the process does indeed exhibit self-limiting growth, with a saturation growth-per-cycle (GPC) of 0.40 ± 0.01 Å (ESI Fig.…”
Section: Resultssupporting
confidence: 63%
“…Using O 3 as an oxygen source for growth of Nb 2 O 5 with Nb (OEt) 5 has, however, remained unexplored until very recently, when Kukli et al utilized O 3 to deposit multilayers of SiO 2 + Nb 2 O 5 for use as a switching media. 25,26 This study confirms that the O 3 process provides films with very low hydrogen content, albeit very little is known regarding the mechanism of growth. As a starting point, we confirmed that the process does indeed exhibit self-limiting growth, with a saturation growth-per-cycle (GPC) of 0.40 ± 0.01 Å (ESI Fig.…”
Section: Resultssupporting
confidence: 63%
“…The niobium to silicon atomic ratio was varied in the range of 0.11-7.20. A detailed description of this sample can be found in reference [7]. In Figure 2 we observe a complete voltage current cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The atomic ratios of niobium to silicon ranged from 0 to 0.13. The films were amorphous in the as-deposited state [11]. The structure of the stacks subjected to the measurements was Al/Ti/SiO 2 :Nb 2 O 5 /TiN/Si, where the top electrodes were made by electron beam evaporation through a shadow mask.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study [11], Nb 2 O 5 -SiO 2 multilayers and mixed films were deposited on TiN electrode substrates by ALD using niobium pentaethoxide, hexakis(ethylamino) disilane, and ozone as precursors, and their ability to perform as resistive switching media in as-deposited state was examined. The conduction currents in single, non-mixed, SiO 2 and Nb 2 O 5 films tended to remain too high to enable reliable switching between high and low resistance states.…”
Section: Introductionmentioning
confidence: 99%